Analisis Kemampuan Penalaran Matematis Siswa pada Materi Pola Bilangan Ditinjau Dari Kemampuan Menyelesaikan Soal Berbasis Masalah - Arsiullahnur R. Paputungan; Ismail Djakaria; Yamin Ismail (Scimadly Publishing, 2024)
This research is a qualitative descriptive study which aims to determine students' mathematical reasoning abilities in solving problem-based questions with categories of high, sufficient and low mathematical reasoning abilities. The subjects studied were 18 students at SMPN 15 Gorontalo who were in class VIII. The data collection technique is a means of collecting data by researchers which takes place in two stages, namely tests and interviews. The indicators used in this research are as follows: 1) Ability to present mathematical statements in writing. 2) submit an opinion. 3) carry out mathematical manipulations. 4) compiling evidence, providing reasons or evidence for the truth and 5) drawing conclusions. The research results showed that the ability to present mathematical statements obtained a presentation of 68.52% in the high category, the ability to put forward conjectures in the presentation 44.44% in the sufficient category, the ability to manipulate mathematical presentations in the sufficient category 44.44%, the ability to draw conclusions, compile evidence, provide reasons or evidence for the correctness of the solution. obtained presents 48.15%. sufficient category, an interesting conclusion from the statement obtaining a percentage of 40.74% in the sufficient category.